2011
DOI: 10.1021/ac2014788
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Spectrofluorimetric Analysis of Single-Walled Carbon Nanotube Samples

Abstract: A new method and instrumentation are described for rapid compositional analysis of single-walled carbon nanotube (SWCNT) samples. The customized optical system uses multiple fixed-wavelength lasers to excite NIR fluorescence from SWCNTs individualized in aqueous suspensions. The emission spectra are efficiently captured by a NIR spectrometer with InGaAs multichannel detector and then analyzed by a computer program that consults a database of SWCNT spectral parameters. The identities and relative abundances of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 32 publications
2
38
1
Order By: Relevance
“…This assumption is based on the effective deprotonation of the thiol group and also supported by the fact that such thiol-containing compound as dithiothreitol (DTT) is the strong reducing agent which increases essentially the nanotube PL QY [9,11,12]. PL spectra of SWNT:ssDNA at every cysteine concentration were fitted with a sum of curves described by a function similar to the Voigt function [17]. The area of each curve was matched with the PL integral intensity of appropriate nanotube species.…”
Section: Cysteine Influence On Spectral Properties Of Swnts Covered Wmentioning
confidence: 99%
“…This assumption is based on the effective deprotonation of the thiol group and also supported by the fact that such thiol-containing compound as dithiothreitol (DTT) is the strong reducing agent which increases essentially the nanotube PL QY [9,11,12]. PL spectra of SWNT:ssDNA at every cysteine concentration were fitted with a sum of curves described by a function similar to the Voigt function [17]. The area of each curve was matched with the PL integral intensity of appropriate nanotube species.…”
Section: Cysteine Influence On Spectral Properties Of Swnts Covered Wmentioning
confidence: 99%
“…Additionally, fluorescence efficiency of DNA:SWCNT was greater than that of SC:SWCNT, suggesting DNA is more effective at dispersing individual SWCNTs than SC, which was expected [12,24,26]. Fluorescence efficiency is a relative measure of dispersion with the principle being that more well-dispersed SWCNTs have greater fluorescence output for a given concentration, which is measured by absorbance [31,32]. By virtue of photoluminescence from both DNA:SWCNT and SC:SWCNT, fluorescence efficiency measurements suggest that the SWCNTs are well-dispersed in solution as expected.…”
Section: Swcnt Preparation and Characterizationmentioning
confidence: 96%
“…This software also calculated the SWCNT diameter distribution from the absorbance and integrated fluorescence measurements. Fluorescence efficiency measurements, which are fluorescence power collected across the emission spectrum for a single excitation wavelength divided by the absorbance spectrum, are reported as a relative measure of SWCNT dispersion in solution [31,32].…”
Section: Characterization Of Dna:swcnt and Sc:swcntmentioning
confidence: 99%
“…However, these authors indicated that the local environment of the CNTs and reabsorption at high concentrations affect the overall photoluminescence intensity. Recently, Rocha et al [104] described a new characterization method for SWCNTs based on a customized NIR fluorescence instrument that employed multiple fixedwavelength lasers for nanotube excitation. The emission spectra obtained were analyzed using a SWCNT spectral database and the type and relative distribution of the bulk sample were rapidly displayed.…”
Section: Fluorescence Spectroscopymentioning
confidence: 99%